Perbandingan Fisik dan Organoleptik Antara Marshmallow dengan Bahan Dasar Gelatin yang Berbeda - Zulfan Mustika Sakti Surya Putra; Suhardi Suhardi; Zakaria Husein Abdurrahman (Tropical Animal Science, 2021)
This study aims to determine the comparison of physical and orgnoleptic qualities between marshmallows made from chicken claws and cow skin with the parameters being tested for taste, chewiness, texture and preference. This research was conducted in July-August 2020 at the laboratory of the Boyolali Veterinary Public Health Service Center and tested on panelists at the Daarul Arqom Tulung Modern Islamic Boarding School, Klaten. The material used consists of two, namely raw materials and manufacturing tools. First, the materials used to make gelatin in this study include chicken claws, cow skin, acetic acid, water, sodium disulfide S), calcium hydroxide ( ) and HCl. Meanwhile, the ingredients used include chicken claw gelatin, cow skin gelatin, vanilla, sucrose syrup, sugar, cornstarch, sugar flour and water. The tools used include basins, measuring cups, scales, scissors, waterbath (water bath), filter paper, vacuum filters, oven and blender. The results of the analysis of various organoleptic tests in this study which included texture, chewiness, taste and liking had a significant difference of P <0.01, namely that marshmallows with cowhide were better than marshmallows with chicken claw as the basic ingredient. The conclusion of the comparative study between marshmallow with gelatin as a base ingredient of cow skin gelatin is superior to that of chicken claw gelatin. Keywords:marshmallow, cowhide, chicken claw